GATHBANDHAN: A CULTURAL ANALYSIS OF THE RITUALS AND THE PRACTICES OF MARRIAGE SYMBOLIZING SUSTAINABILITY - Davis, Antony; Mukherjee, Panchali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study focuses on the vital intersection of environmental and cultural sustainability within event tourism, specifically emphasising marriage events. As the demand for unique and memorable wedding experiences continue to rise, this chapter delves into how event planners and participants can contribute to environmental preservation and cultural enrichment. By examining the strategies and practices that promote sustainability in marriage rituals and events, this study offers insights into creating meaningful celebrations that leave a positive legacy for both the environment and cultural heritage. The chapter “Gathbandhan: A Cultural Analysis of the Rituals and the Practices of Marriage Symbolizing Sustainability” critically analyses the various sustainable rituals and practices related to marriage using the cultural theory. The academic study is interdisciplinary as it focuses on different areas such as culture, economy, society, environment etcetera. The study focuses on representation as a key feature of cultural theory. The marriage rituals and practices are represented as icons, symbols, and indices embedded in various cultures which are also markers of sustainability. Some practices provide an alternative to technological hegemony in modern times. The study depicts the marriage rituals or practices as signs embedded in a network of signs where the signifier is the ritual or practice studied and the signified is the idea of multifaceted sustainability. The academic study views marriages with their varied rituals and practices as cultural texts with a politics of reception. The various rituals and practices of marriages depict consumption, a chief tenet of cultural theory as a route to sustainable economic growth. The study attempts to rehabilitate the traditional marriage rituals and practices that have been marginalized in modern times by focusing on them and proving them to be markers of sustainability.